Giant meningoencephalocele with Arnold-Chiari type III malformation and anaesthetic challenges: A rare case report - Ganeriwal, Veena (Saudi J Anaesth, 2019)
Meningoencephalocele means protrusion or herniation of brain (neural) tissue along with meninges through a defect in the cranium into a swelling filled with cerebrospinal fluid (CSF). It is very rarely associated with Arnold-Chiari type III (ACM type III). Size, location and type of content of the swelling determine the surgical as well as anaesthetic problems. The most common challenges faced by anaesthesiologist in managing these patients are related to positioning of head and prevention of rupture of swelling, airway management, fluid and blood loss and maintenance of body temperature. In order to manage huge meningoencephalocele, you need a well-planned approach amongst anaesthesiologist and surgeon.